Molecular characterization of a potyvirus infecting tuberose (Polianthes tuberosa) in southern India - DEVARAJU and S. JALALI, M. KRISHNAREDDY*, R. SMITHA (Indian Phytopathology, 2007)
Tuberose plants showing symptoms of mosaic, mottling and in severe cases reduced tillering and stunted growth were observed in farmers fields. The incidence ranged from 7.5 to 75.6% in different fields surveyed in Andhra Pradesh, Karnataka and Tamil Nadu states. The virus was mechanically transmitted to tuberose but not to 16 other test plants species. Crude extract of infected leaves of tuberose plants showed presence of flexuous filamentous particles approximately 730 nm in length and 12 nm in diameter under electron microscope. In ELISA, weak serological relation was observed between BBrMV, SCMV and not with BYMV, ChiVMV, CdMV, MDMV,and PVY. Using RT-PCRwith primers specific for potyviridae, a PCR product of 1.7kb was amplified from infected plants but not from healthy plants. Cloning and sequencing of the PCR DNA fragment revealed that the cloned DNA fragment consisted of 1663 nucleotides with a single continuous open reading frame of 1494 nucleotides. This includes part of the region encoding the replicase (Nib), the entire coat protein-coding region followed by 149 nucleotides of the 3' UTRand a poly A tail. Multiple alignment analysis revealed that the partial polyprotein of TuMMoV-Banaglore had highest homology of 88.9%at aa and 84.0 % at nt level with TuMMoV-Hangzhou. Phylogenetic analysis of coat protein amino acid sequences demonstrated that TuMMoV-Banaglore branched as subgroup along with WLMoV and OV3. Sequence comparison of 3' UTR revealed homology levels of 9.3 to 57.0% between potyviruses and 89.7 to 98.7% with TuMMoV isolates. Based on sequence homology of coat protein and 3'UTR TuMMoV-Banaglore has been identified as distinct strain of TuMMoV which is different from TuMMoV-Hangzhou and TuMMoV-Palampur.